2021
DOI: 10.1002/art.41736
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Epigenetic Fine‐Tuning of TGFB1 Expression Within the Human Osteoarthritic Joint

Abstract: Objective Osteoarthritis (OA) is an age‐related disease characterized by articular cartilage degeneration. It is largely heritable, and genetic screening has identified single‐nucleotide polymorphisms (SNPs) marking genomic risk loci. One such locus is marked by the G>A SNP rs75621460, downstream of TGFB1. This gene encodes transforming growth factor β1, the correct expression of which is essential for cartilage maintenance. This study investigated the regulatory activity of rs75621460 to characterize its impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…Tc28a2 immortalised chondrocytes [ 22 ] were seeded onto a 96-well plate at 5000 cells/well and transfected 24h later with 100ng pCpG-free-promoter DNA and 10ng pGL3-promoter (Promega) with Lipofectamine 2000 (Invitrogen). Cells were lysed after 24h and luminescence was read using the Dual-Luciferase Reporter Assay System (Promega) [ 15 ]. Six biological replicates were performed for each plasmid construct.…”
Section: Methodsmentioning
confidence: 99%
“…Tc28a2 immortalised chondrocytes [ 22 ] were seeded onto a 96-well plate at 5000 cells/well and transfected 24h later with 100ng pCpG-free-promoter DNA and 10ng pGL3-promoter (Promega) with Lipofectamine 2000 (Invitrogen). Cells were lysed after 24h and luminescence was read using the Dual-Luciferase Reporter Assay System (Promega) [ 15 ]. Six biological replicates were performed for each plasmid construct.…”
Section: Methodsmentioning
confidence: 99%
“…TGFB1 of course encodes a ligand of the TGF-beta superfamily, with the pathway well described to regulate cartilage development and tissue homeostasis 24 . Rice et al demonstrated differential enhancer activity and protein binding per allele 25 . CRISPR-Cas9-mediated deletion of the locus implied regulation of only TGFB1, and correlation between DNA methylation of CpGs adjacent to the rs75621460 and TGFB1 expression were found, especially in cartilage tissue.…”
Section: Functional Genetic Analysismentioning
confidence: 99%
“…Rice et al. demonstrated differential enhancer activity and protein binding per allele 25 . Clustered regularly interspaced short palindromic repeats (CRISPR)-Cas9-mediated deletion of the locus implied regulation of only TGFB1 , and correlation between DNA methylation of CpGs adjacent to the rs75621460 and TGFB1 expression were found, especially in cartilage tissue.…”
Section: Geneticsmentioning
confidence: 99%
“…OA genetic susceptibility loci and SNPs have been largely superseded by hypothesis-free genome-wide association scans [ 67 ]. For example, a strong correlation between DNA methylation and transforming growth factor-β (TGF-β) expression was observed in OA patients [ 68 ]. An SNP located within the TGF-β enhancer region, rs75621460, impacted the activity of the enhancer, and showed protective effects in the cartilage and the synovium.…”
Section: Cellular Hallmarks Of Aging In Oa Chondrocytesmentioning
confidence: 99%